Labor requirements for handling manure from concrete basins - Joseph P. Harner; T. Strahm; David V. Key; T. L. Strahm (Kansas Agricultural Experiment Station Research Reports, 1999)
Time requirements for loading a manure spreader and traveling to and from the field varied from 20 to 30 min per load. However, standardizing the data showed that 5 to 7 min were required per 1,000 gal (9,000 lb). The preliminary results of the time motion data indicate about 30 min per cow per year are required for handling manure from a concrete storage basin. These results were consistent among the four dairies evaluated, even though differences existed in operating procedures. These results enable dairy producers to assess labor and equipment needs for performing the various operations associated with hauling manure from a concrete storage basin.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Manure; Handling; Labor; Storage